Sustainable Production of Vanillin from Vanillyl Alcohol, a Model Compound of Lignocellulosic Biomass Conversion, via Selective Heterogeneous Catalysis - Latorre, Daiana Cecilia; Lick, IIeana Daniela; Merlo, Andrea Beatriz; Ballesteros-Plata, Daniel; Rodríguez-Castellón, Enrique; Casella, Mónica Laura; Faroppa, María Laura; Musci, Juan José (Applied Science and Engineering Progress, 2025)
Vanillin, a flavoring agent, is used extensively in the food industry. It is primarily derived from a petroleum derivative through synthetic procedures, though these technologies present certain drawbacks, including the generation of undesired byproducts and a relatively low yield. Furthermore, residual lignocellulosic biomass serves as a renewable source of aromatic compounds with the potential to be used as raw material in the synthesis of vanillin. This would allow the valorization of the residue, resulting in the production of a highly demanded compound for the food industry. To achieve this objective, a heterogeneous Pd catalyst supported on alumina was prepared and its activity was investigated in the oxidation reaction of vanillyl alcohol, a model compound of lignin, to obtain vanillin. The impact of key reaction parameters, including temperature, oxidant concentration, pH of the medium, and solvent, was evaluated. The Pd(1%)/Al₂O₃ catalyst used was capable of achieving 84% conversion and selectivity over 99% towards vanillin under mild conditions after a 3-hour reaction period in an alkaline medium using water as a solvent.